Emotion's role in the unity of consciousness - Doulatova, Maria (Philosophical psychology, 2021)
In subjects with the split-brain syndrome, some conscious states appear to be disunified (e.g., visual states), while others remain unified (e.g., affective states). While placing emphasis on the disunities, disunity accounts conclude that split-brain subjects have two subjective perspectives and not one. I argue that affective unity is more important than perceptual disunity in delineating our subjective perspective. Unlike enjoying an objective perspective, enjoying a subjective perspective entails experiencing aspects of your phenomenal field in terms of their overall relation to you. What it's like to be you at any given time entails experiencing certain aspects of the phenomenal field as peripheral to others. Emotion creates and sustains a center/periphery structure in our phenomenal field by signaling orders of perceived importance as well as orders of perceived changeability (e.g., to someone feeling grief, the experience of getting a ticket is felt as peripheral/unimportant to the experience of grief; to someone feeling depressed, the experience of reaching a hilltop is felt as peripheral/unattainable to the experience of laying down to rest). Since emotion plays a greater role than perception in creating and sustaining this periphery/center structure, and split-brain patients remain affectively unified, split-brain patients retain a unified subjective perspective on the world.